The Role of Actuarial Accounting in Achieving Financial Sustainability - Hussien Sabea Khamees (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study aims to examine actuarial accounting, the role of actuary accountants, and their contribution to enhancing corporate financial sustainability, particularly in companies with long-term financial obligations. Methodology: The study uses a conceptual and descriptive-analytical approach by reviewing relevant literature on actuarial accounting, risk assessment, and long-term financial planning in corporate finance. Results: The findings indicate that actuarial accounting plays an important role in strengthening corporate financial sustainability by supporting long-term financial planning and improving risk identification. Actuary accountants contribute significantly by utilizing statistical and historical data to predict future financial events and assess potential risks, thereby enhancing the accuracy of financial forecasting and planning. Conclusions: The study concludes that actuarial accounting is essential for improving companies’ long-term financial sustainability. The involvement of actuary accountants in financial decision-making processes helps organizations optimize resource allocation and strengthen strategic financial planning. Limitations: This study is limited to a conceptual analysis based on existing literature and does not include empirical data or case-based validation. Contribution: This study contributes to the literature by emphasizing the importance of actuarial accounting and actuary accountants in improving long-term financial sustainability and supporting more effective corporate decision-making processes.